How Old is Too Old? Closure of Patent Foramen Ovale in Older Patients - Carlos Vazquez-Sosa; Stacey D Clegg; James C Blankenship (US Cardiology Review, 2021)
Percutaneous closure of a patent foramen ovale (PFO) reduces the risk of recurrent cryptogenic stroke specifically in younger patients. The three randomized controlled trials that led to the widespread adoption of PFO closure excluded patients over the age of 60 years. Older patients frequently have other cardiac and vascular conditions that are common risk factors for stroke, whereas paradoxical embolism through a PFO is relatively rare. Younger patients theoretically benefit the most from closure due to longer lifetime exposure risk and absence of other traditional risk factors. PFO in older patients with cryptogenic strokes is often encountered in clinical practice, making up an increasing number of cardiology referrals, yet cardiologists lack guidelines and evaluation tools for these patients. This review explores the history of PFO closure – emphasizing data in older adults – and discusses the evaluation and treatment of older people with cryptogenic stroke and PFO while further trials in this important population are awaited.